Electrolytic deposition of reactive element thin films on Crofer 22 APU and evaluation of the resulting high-temperature corrosion protection properties at 700 °C–900 °C. (12th September 2022) - Lemieszek, Bartłomiej; Ignaczak, Justyna; Kamecki, Bartosz; Karczewski, Jakub; Mogensen, Mogens Bjerg; Molin, Sebastian; Jasiński, Piotr
Abstract: This article presents electrolytic deposition of thin Rare Earth (RE) coatings on Crofer 22 APU stainless steel substrates for high temperature applications, such as interconnects in solid oxide cell stacks. The deposition of coatings based on yttrium-, gadolinium-, lanthanum-, and cerium nitrates is discussed. The high temperature corrosion properties of surface-modified steels were examined using thermogravimetry and electrical resistivity measurements. Coatings and oxide microstructures were examined by XRD and SEM of surfaces and cross-sections. The results showed that the use of the RE element oxide layers reduced the growth of oxide scale, as evidenced by lower weight gain. The layers based on Y- and Gd-oxides showed the best corrosion protection properties. The electrical measurements showed that the surface-modified samples had lower resistance than the uncoated sample. Highlights: New technique of obtaining thin ceramic layers - electrolytic technique. Electrolytic deposition of cerium, gadolinium, lanthanum and yttrium oxide layers. Thin ceramic layers, on the order of tens of nanometers. Reduction of the thermogravimetric weight gain of samples covered with a ceramic layer. Electrical measurements showed that the surface-modified samples had lower resistance than the uncoated sample.